Implementasi Layanan Konseling Dengan Metode Reinforcement Guna Meningkatkan Motivasi Belajar Pada Siswa SMK Negeri - Rahmayanti, Rahmayanti (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2023)
Research aims; 1) to reveal the effect of the Reinforcement method on the learning motivation of students at SMK Negeri 3 Bantaeng, 2) Want to know how far the creativity of students in learning after the application of the Reinforcement method to students at SMK Negeri 3 Bantaeng Class X. This research is an action research (action research), because the research was conducted to solve learning problems in the classroom. This research also includes descriptive research, because it describes how a learning technique is applied and how the desired results can be achieved. This research was conducted at SMK Negeri 3 Bantaeng, Tanetea Village, Pa'jukukang District. This study uses a qualitative descriptive analysis technique. To analyze the success rate or percentage of student success after the teaching and learning process each round is carried out by providing an evaluation in the form of a practice test at the end of each round. This analysis is calculated using simple statistics. The results of learning activities that have been carried out for two cycles and based on all the discussion and analysis that have been carried out can be concluded as follows: 1) Counseling Guidance Services with this method have a positive impact on increasing student learning motivation which is marked by an increase in student achievement scores in each cycle, namely cycle I (72%), and cycle II (93%), 2) The application of this guidance counseling service method has a positive influence, namely it can increase student learning motivation as indicated by the average student answer which states that students are interested and interested in this learning method so that they become motivated to learn.